Ex ante economic impact assessment of the 3R-gene potato in Kenya. - Evelyne Kihiu; Marc Ghislain; Anthony Mwangi Kibe; Ng'ang'a Nancy; Marcel Gatto; Jose B Falck-Zepeda (PLoS ONE)
Potato late-blight disease is as a major constraint to potato production in Kenya. The use of fungicides to control the disease is limited by the practice of delaying application until the symptoms are visible, and inappropriate application rates and methods. Biotech crops, such as 3R-gene potato, are providing sustainable solutions to crop protection challenges in agriculture, but little is known about their social and economic potential in any country. To gain greater insights into the potential of 3R-gene potato in Kenya, this study evaluates the economic benefits of Asante, Shangi, and Tigoni potato varieties, which are resistant to late blight. Data from experts along the potato value chain and secondary sources are analyzed using the economic surplus model and a real options model. First, experts' opinions revealed that late-blight disease is responsible for 23% of production loss annually, and that 12% of the production costs are due to the use of fungicides to control late blight disease. Secondly, the study results suggest that the release of 3R-gene Shangi would generate the greatest economic benefits of KES 845.9 million (US$ 8.2 million) annually. The expected net benefits of 3R-gene Asante are KES 7.3 million (US$ 0.07 million) annually. 3R-gene Tigoni, with the lowest potential adoption rates, would be expected to realize a negative net of KES of -1.26 million (US$ -0.01 million) annually. Significant potential economic gains, which is expected to increase with better awareness of biotech crops, support the immediate release of 3R-gene Shangi in Kenya.